Poznavanje vsebine kompleta za prvo pomoč med vozniki motornih vozil - Šterbenc, Irena (Obzornik zdravstvene nege, 2009)
Introduction: By the number of the deceased in traffic accidents, Slovenia belongs to the less safe countries of the European Union. In case of a trafficaccident with injured people, first aid can prevent worsening of the condition, handicap or death of the affected persons. In order to provide immediate first aid, a first aid kit is a necessary and compulsory safety itemin all motor vehicles. The purpose of the research was to determine whether motor vehicles are equipped with the necessary (old or new) first aid kit and whether motor vehicle drivers are familiar with the contents of the first aid kit and maintain it properly. Methods: A descriptive method of research was applied. The data were gathered through March and April 2008 withthe use of a questionnaire. Included in the study were 128 randomly chosenmotor vehicle drivers (63 female and 65 male) from Dolenjska and Bela Krajina regions. Results: All participants but one had the first aid kit in their vehicle. 29.7 % of the respondents had the old first aid kit and 68.8 % the new one. The majority of the participants did not know which of the listeditems belong to the old kit and which ones to the new one. Their knowledge of the first aid kit individual items was also insufficient. The first aid bandage was best known article among the drivers. The used up material from the kit is rather quickly replaced with the new one by the majority of respondents, whereas only one third check the material expiration date of the first aid kit at least once a year. Discussion and conclusion: A low level of knowledge of the first aid kit contents has been confirmed. It istherefore necessary to focus more attention to motor vehicles drivers' awareness about the first aid kit supplies, the purpose of particular items and their correct usage. It should be pointed out that nurses play an important role in providing and delivering proper information on the issue. They outnumber all other professionals holding licence by the Slovenian Red Cross Centre for First Aid Education training motor vehicle drivers on first aid delivery. This responsibility is mandated to nurses also by the ethical code of their profession.
Keywords: komplet za prvo pomoč; motorna vozila; prometne nesreče; prva pomoč